2017
DOI: 10.1039/c7en00152e
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of magnetite nanoparticle mobility in a heterogeneous flow cell

Abstract: Measured and simulated magnetite nanoparticle transport and retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Retention and formation damage parameters vary with the different rock and NP encapsulation types and are usually determined by column experiments. In this case, experimental NP retention parameters are adopted from a large-scale lab experiment ( [10]). Formation damage is also considered by assuming the maximum permeability reduction is 50%, which means the formation damage coefficient, β adsorption , can be calculated based on Eq.…”
Section: Case 5: Encapsulation Conformance Control In a 3d Reservoirmentioning
confidence: 99%
See 1 more Smart Citation
“…Retention and formation damage parameters vary with the different rock and NP encapsulation types and are usually determined by column experiments. In this case, experimental NP retention parameters are adopted from a large-scale lab experiment ( [10]). Formation damage is also considered by assuming the maximum permeability reduction is 50%, which means the formation damage coefficient, β adsorption , can be calculated based on Eq.…”
Section: Case 5: Encapsulation Conformance Control In a 3d Reservoirmentioning
confidence: 99%
“…These sur-2 face interactions, in turn, can result in reversible or irreversible capture ( [9]). Additionally, density differences can make NPs respond to gravity or inertial flows in ways that solutes do not ( [10]). Finally, engineered behaviors such as payload release or triggered responses add a more complex reaction component to the modeling, compared to traditional advective-dispersive-reactive transport ( [11,12] Our understanding of basic NP behavior in porous media is founded on a long history of experiments and theory on colloids and interfaces, particularly examples such as ( [13]; [14]; [15]; [16]; [17] and [18]).…”
Section: Introductionmentioning
confidence: 99%
“…3), with subsequent transport captured via digital imagery. We used similar data collection techniques to those previously employed in investigations of the migration of solute plumes affected by density gradients in porous media [22,27,32]. Two different concentrations of carbon ink, 2.07 g L -1 and 10.33 g L -1 , were used to investigate effects of changing density gradients.…”
Section: Flume Experimentsmentioning
confidence: 99%
“…Like solutes, nanoparticles can change the density of the carrier fluid. Consequently, nanoparticle concentration variations can result in fluid density gradients that affect both fluid flow and mass transport processes [22,26,27]. Jin et al [28] showed that such density gradients can accelerate solute transfer from the river water to the riverbed and inhibit the release of solutes from the bed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation